2023
DOI: 10.1111/iwj.14308
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain‐based enzymatic burn debridement: A systematic review of clinical studies on patient safety, efficacy and long‐term outcomes

Abstract: In 2012 the European Medicines Agency approved a pineapple stem‐derived Bromelain‐based debridement concentrate of proteolytic enzymes (NexoBrid®, MediWound Ltd, Yavne, Israel) for adult deep burns. Over 10 000 patients have been successfully treated with NexoBrid® globally, including in the US. The aim of our study is to perform a systematic review of the current literature on Nexobrid® outcomes. We conducted a literature search in PubMed, Google Scholar, Embase, and other search engines (2013–2023). The onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 96 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…Some studies have confirmed the safety of NexoBrid in the treatment of adult and pediatric burns [ 71 ], while Shoham et al [ 73 ] showed better results in children than in adults. Given the higher prevalence of burns in children (approximately 60%) and the important emotional and health significance of this condition, the use of enzymatic debridement for early eschar removal in the pediatric population is an important challenge to achieve a good long-term outcome [ 73 ].…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have confirmed the safety of NexoBrid in the treatment of adult and pediatric burns [ 71 ], while Shoham et al [ 73 ] showed better results in children than in adults. Given the higher prevalence of burns in children (approximately 60%) and the important emotional and health significance of this condition, the use of enzymatic debridement for early eschar removal in the pediatric population is an important challenge to achieve a good long-term outcome [ 73 ].…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of NexoBrid in selectively removing burn eschar in a single 4-hour application, thus reducing the necessity for surgical excision of necrotic tissue [ 73 ] by at least 3.5 times [ 71 ] and preserving dermal tissue [ 72 ]. In addition, NexoBrid provided faster wound healing with better long-term outcomes [ 73 ] and improved quality of life [ 72 ].…”
Section: Use Of Bromelain In Children and Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although EDNX has become a standard procedure in many burn centers worldwide during the past ten years, surprisingly, our recent extensive search of the literature showed limited valid data on the long-term scarring after the enzymatic debridement of the hands. Shoham et al conducted a systematic review in 2023, finding 103 relevant studies, of which 34 were found eligible [ 10 ]. Among these, there were several studies investigating the long-term outcomes of hand burns after enzymatic debridement.…”
Section: Introductionmentioning
confidence: 99%